Clinical factors affecting the long-term survival of breast cancer patients. Issue 3 (March 2023) - Li, Yong-Hui; Wang, Xiao-Ying; Shen, Jun-Wei; Ma, Lin-Lin; Wang, Cui-Ping; He, Kai; Liu, Ding-Sheng; Li, Yan-Fei
Objective: The average 5-year survival rate of breast cancer (BC) patients has been significantly prolonged with new therapeutic methods. However, their effects on BC patient long-term survival rates are unclear. Therefore, this study aimed to analyze the specific clinical factors that can affect BC long-term survival. Methods: Here, we conducted a retrospective study and analyzed long-term survival using data of 3, 240 BC patients from 1977 to 2005 from the Genotype-Tissue Expression (GTEx) database using the Kaplan–Meier method. Results: Breast tumor size and stage were negatively correlated with long-term survival, but age showed no significant correlation. Estrogen receptor (ER) and progesterone receptor (PR) expression were each positively correlated with patient survival time, while ERBB2 receptor (HER2) expression was negatively correlated with survival time. Patients with high Nottingham prognostic index (NPI) values did not benefit from available therapies. Furthermore, breast-conserving surgery is more conducive to BC patient long-term survival than mastectomy. Conclusions: Early detection and breast-conserving surgery may support long-term survival for BC patients. Elevated expression of ER and PR were both associated with longer patient survival time, while positive expression of HER2 showed the opposite trend. The long-term survival rates of patients with high NPI values can potentially be increased.